Supercapacitors Theoretical and Practical Solutions - Liudvinavičius, Lionginas (IntechOpen, 2018)
This edited volume Supercapacitors: Theoretical and Practical Solutions is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of electronic devices and materials. The book comprises single chapters authored by various researchers and is edited by a group of experts. Each chapter is complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on electronic devices and materials and opens new possible research paths for further novel developments.